Collection and morphological characterization of Panicum coloratum L. in Argentina - Armando, Lorena; Carrera, Alicia Delia; Tomas, Maria Andrea (2018)
Panicum coloratum (Poaceae) is a perennial grass native to South Africa, distributed all over the world, but poorly adopted by ranchers in Argentina. Adapted to a wide range of soil and climatic conditions, it constitutes a good forage resource for zones with edaphic and climatic restrictions, where cattle rising activities are here displaced. The high polymorphism in the species has made it difficult to delineate sub specific taxonomic categories. It has been classified in botanical varieties, types and/or cultivars. In order to document the morphological variability in P. coloratum and to investigate the differences between var. makarikariense and var. coloratum, a collection was gathered in INTA Rafaela composed by fourteen accessions from different provinces of Argentina: six accessions of var. makarikariense and eight from var. coloratum. The evaluation of 152 individuals gives evidence of a wide morphological variation in the collection in traits related to forage and caryopses production; seven out of nine traits showed significant differences between var. makarikariense and var. coloratum. Based on the study of local type specimens, a morphological key to distinguish between P. coloratum varieties is provided. These results report new information about the diversity in P. coloratum in Argentina and provide valuable insights for future use of the collection as the base material of a breeding program.